VoIP on Wireless Meshes: Models, Algorithms and Evaluation - Kashyap, A.; Ganguly, S.; Das, S.R.; Banerjee, S. (IEEE INFOCOM 2007 - 26th IEEE International Conference on Computer Communications, 2007)
We study the problem of supporting VoIP calls in a wireless mesh network. Specifically, we propose solutions for call admission control (CAC) and route selection for VoIP calls. Call admission decisions must evaluate how the capacity of the mesh network is utilized by the existing calls. We address this issue via a measurement-based modeling effort to model mutual interference between wireless links. The modeling approach evaluates whether capacity constraints (or, required QoS metrics) will be satisfied if a new call is admitted with a given route. Evaluations with a 6-node 802.11a testbed demonstrate excellent accuracy of the model and thus also the CAC performance. We address the issue of route selection by also using a modeling approach that considers models of transmission and interference ranges to develop a polynomial-time algorithm to search for feasible routes. This problem takes exponential time for wireless networks without such modeling. In addition to studying feasibility, we study several routing metrics such as shortest feasible path and maximum residual feasible path. Finally, we develop a new method for routing using call statistics that uses prior calling patterns to avoid potentially critical links. We evaluate the performance of these route selection techniques via extensive simulations and demonstrate the superiority of using max residual feasible path over simply shortest feasible path, and routing using call statistics over max residual feasible path.